PTU-097 Long-term effect of obeticholic acid on transient elastography and ast to platelet ratio index in patients with pbc. (17th June 2017) - Hirschfield, GM; Floreani, A; Trivedi, PJ; Pencek, R; Liberman, A; Marmon, T; MacConell, L
Abstract : Introduction: The AST to Platelet ratio (APRI) and transient elastography (TE) have both been identified as being predictive of adverse outcomes in primary biliary cholangitis (PBC). Obeticholic acid (OCA) is a farnesoid X receptor (FXR) agonist indicated for the treatment of PBC in combination with ursodeoxycholic acid (UDCA) in adults with an inadequate response to UDCA, or as monotherapy in adults unable to tolerate UDCA. Using the randomised, double-blind (DB), placebo (PBO)-controlled Phase 3 study investigating OCA in patients with PBC, along with data from the ongoing open-label extension (OLE) we sought to investigate the effects of OCA on established non-invasive measures of liver fibrosis and outcomes in PBC. Method: We re-evaluated patients randomised and dosed in OCA 10 mg (n=73), OCA 5–10 mg (n=70, 33 patients titrated from 5 to 10 mg at Month 6), or PBO (n=73) groups during DB treatment. In the OLE, all patients were initially treated with 5 mg OCA with the option to increase to 10 mg (or later decrease) based on response and tolerability every 3 months. Non-invasive measures of liver fibrosis that were assessed were APRI and liver stiffness measurements (LSM) by transient elastography. Results: APRI was significantly reduced from baseline to DB Month 12 in both OCA–treated groups compared to PBO (p<0.01). PBO patients who initiated OCA during the OLE phase and patients randomised to OCA 5–10 mg had significant reductions from baseline to OLE Month 12 in mean APRI score (p<0.05). The mean APRI score in OCA 10 mg was reduced, but not significant at OLE Month 12 compared to baseline. During DB and OLE phases, while not significant, the OCA 10 mg group had mean reductions in LSM, while both OCA 5–10 mg and PBO groups had mean increases in LSM (Table). Conclusion: Both LSM and APRI, as non-invasive measures of liver fibrosis, have been found to be effective in predicting outcome in patients with PBC. DB and OLE treatment with OCA resulted in a mean reduction in liver stiffness and significant improvements in APRI suggesting that with long-term use, OCA has the potential to improve long term outcomes for patients. Disclosure of Interest: G Hirschfield: None Declared, A Floreani: None Declared, P Trivedi: None Declared, R Pencek Conflict with: Intercept Pharmaceuticals, Inc., Conflict with: Intercept Pharmaceuticals, Inc., A Liberman Conflict with: Intercept Pharmaceuticals, Inc., Conflict with: Intercept Pharmaceuticals, Inc., T Marmon Conflict with: Intercept Pharmaceuticals, Inc., Conflict with: Intercept Pharmaceuticals, Inc., L MacConell Conflict with: Intercept Pharmaceuticals, Inc., Conflict with: Intercept Pharmaceuticals, Inc.